EU counter-terrorism offences What impact on national legislation and case-law? - Barbe, Emmanuel (European Studies, 2012)
To several governments, modern international terrorism cannot be handled adequately within the ordinary criminal justice system. To fight terrorism (including the criminalization of certain "abstract danger", preparatory activities such as terrorist training, membership in a terrorist organization) more effectively, criminal law had to be adapted.